2012
DOI: 10.5455/2319-2003.ijbcp002412
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of voglibose versus pioglitazone on glycaemic control and lipid profile in patients of type 2 diabetes mellitus on glimepiride and metformin in punjabi population

Abstract: Background: Type 2 Diabetes mellitus (DM) is a heterogeneous group of disorders associated with both microvascular and macrovascular complications. Due to progressive nature of type 2 DM, dual / triple drug therapy produce additive effects, less side effects and allows the use of submaximal doses of individual agents. Therefore, the present study was designed to study the effect of voglibose in comparison to pioglitazone on glycaemic and lipid profile as an add-on drug in patients with DM whose glycaemic statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…27 The present study observed a mean decline of 1.19±0. 27 30 In present voglibose treatment group a mean reduction of 83.98 and 118.75 mg/dL in PPBG at 3 and 6 months respectively which was statistically significant.…”
Section: Discussionmentioning
confidence: 58%
“…27 The present study observed a mean decline of 1.19±0. 27 30 In present voglibose treatment group a mean reduction of 83.98 and 118.75 mg/dL in PPBG at 3 and 6 months respectively which was statistically significant.…”
Section: Discussionmentioning
confidence: 58%
“…Similarly, study conducted by Amita Jindal et al supports with our study. [25] Moreover, FDC of Metformin with Pioglitazone and FDC of Metformin with Voglibose have an impact on serum Adiponectin and Serum Ghrelin Level and these were increased significantly from baseline to after 6 months. Several previous cross-sectional and longitudinal studies have established that low Adiponectin and Ghrelin levels are associated with increased risk of T2DM.…”
Section: Discussionmentioning
confidence: 94%
“…Glycaemic control : There were 26 studies (13 randomized and 13 non-randomized, controlled, comparative CTs) with primary objective to determine efficacy of pioglitazone in T2DM patients. Eight were monotherapy 43 44 45 46 47 48 49 50 , one add-on to metformin 51 , four add-on to sulfonylurea 52 53 54 55 , and eight were add-on to sulphonylurea and metformin combination 56 57 58 59 60 61 62 63 . Two studies evaluated add-on to metformin, sulphonylurea and insulin 64 65 ; three evaluated and noted decrease in α-amylase, glucokinase and gamma-glutamyl transferase activities 66 67 68 .…”
Section: Resultsmentioning
confidence: 99%